1978
DOI: 10.1177/030089167806400613
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer in Childhood

Abstract: From 1956 to 1975 21 patients (13 females and 8 males) with thyroid cancer developed by age 14 have been observed at the Istituto Nazionale Tumori of Milan. Follicular adenocarcinoma was diagnosed in 4 cases and papillary adenocarcinoma in 17. Five patients (24%) had been given previous cervical irradiation for benign conditions. At admission lung metastases were evident in 2 patients (one affected by follicular and the other by papillary adenocarcinoma). All patients were submitted to surgical treatment, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In Marshallese, exposed to a mixture of radioiodines and gamma radiation, thyroid malignancies were detected 10-21 years after the nuclear explosion [18]. Various studies of childhood thyroid cancers after exposure of the head and neck to external irradiation demonstrate a latent interval of 3.5-18 years, with the average time between X-ray therapy and tumor development varying from 6.3 to 9.6 years [19][20][21][22][23]. The National Council of Radiation Protection and Measurement recommends using a minimum induction period of 5 years in the calculation of risk of radiation-induced thyroid cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…In Marshallese, exposed to a mixture of radioiodines and gamma radiation, thyroid malignancies were detected 10-21 years after the nuclear explosion [18]. Various studies of childhood thyroid cancers after exposure of the head and neck to external irradiation demonstrate a latent interval of 3.5-18 years, with the average time between X-ray therapy and tumor development varying from 6.3 to 9.6 years [19][20][21][22][23]. The National Council of Radiation Protection and Measurement recommends using a minimum induction period of 5 years in the calculation of risk of radiation-induced thyroid cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1970, several additional studies on thyroid neoplasms in children after external X-ray therapy have been published (Table 2). 31,[43][44][45][46][47][48][49][50] Other studies of thyroid carcinoma after different sources of radiation exposure have shown an increase in incidence predominantly in the adult population. Thus, among the hundreds of cases of thyroid carcinoma in atomic bomb survivors of Hiroshima and Nagasaki, we could only find a description of two tumors in ~hi1dren.l~ Seven thyroid neoplasms were documented in residents from the Marshall Islands who were exposed to radioiodines in fallout from the 1954 atmospheric nuclear tests.…”
Section: Discussionmentioning
confidence: 99%
“…PTCs in childhood and adolescence are reportedly characterized by an excellent overall survival (OS), nearing 100%, despite a strong tendency for loco‐regional and distant spread, with very high percentages of invasion beyond the thyroid capsule into the soft tissue of the neck, distant metastases, and recurrences, whereas these prognostic factors negatively characterize the outcome in adult PTC, particularly in the high‐risk, poorly differentiated forms 2–6. If Chernobyl series are excluded, the literature contains only a few large series of PTCs of childhood and adolescence with a long‐term follow‐up 1,7,8–13. Our aim was to evaluate our clinicopathological and follow‐up data on a series of 42 consecutive patients with PTC aged 0–17 years treated at our institution over a 30‐year period, whose histological material was available for review and whose clinical data at onset and during follow‐up were complete.…”
Section: Introductionmentioning
confidence: 99%